The future of humanity revisioning the human in the posthuman age - Radia, Pavlina (Future perfect: images of the time to come in philosophy, politics, and cultural studies., 2019)
This volume offers an interdisciplinary conversation about several possible futures for the human species. The contributors elaborate on the issues that trouble our very understanding of what it means to be human in the 21st century, expanding on recent scholarly discussions about the posthuman and nonhuman turn.